Ownership diversification and product market pricing incentives - Albert Banal-Esta\~nol; Jo Seldeslachts; Xavier Vives (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
We link investor ownership to profit loads on rival firms by the managers of a firm. We propose a theory model in which we distinguish between passive and active investors' holdings, where passive investors are relatively more diversified. We find that if passive investors become relatively bigger, then common ownership incentives increase. We show that these higher incentives, in turn, are linked to higher firm markups. We empirically confirm these relationships for public US firms in the years 2004-2012, where the financial crisis coincides with passive investors' rise. The found effects are small but non-negligible.
Keywords: 330; Common ownership; investor diversification; product markets